Pengaruh Layout Terhadap Minat Beli Ulang - Lestari, Shinta (Universitas Darwan Ali, 2023)
This study analyzes the impact of store layout on costumer’s repurchase intention at the Lariez48 Sampit store, Dila18 Sampit store, and Miracle store. The sample was collected using the accidental sampling method with a total of 100 respondents. We used multiple linear regression for data analysis. The result shows that store layout had no effect on repurchase intention.